Physical Activity Levels and Total Food Intake among Preclinical Students at a School of Medicine and Health Sciences - Halim, Lydia Esterlita; Tjhay, Francisca; Prastowo, Nawanto Agung; , Vetinly; Widjaja, Nelly Tina (Folia Medica Indonesiana, 2023)
Highlights: 1. This is the first cross-sectional study in Indonesia that was conducted specifically to find a correlation between physical activity levels and food intake. 2. As lower physical activity was found to be associated with higher food intake, this study suggests that physical activity might be taken into consideration to manipulate one's food consumption Abstract One of the most crucial things a person can do to enhance the well-being of their body is to engage in regular physical activity. However, currently, there are still many people who have low physical activity levels. It is stated that habitual physical activity can affect the sensitivity of food intake regulation. This study aimed to determine the correlation between the total food intake and physical activity of preclinical students. This study was conducted using the cross-sectional method among preclinical students (n=238) in the classes of 2017, 2018, and 2019 at the School of Medicine and Health Sciences, Atma Jaya Catholic University of Indonesia, Jakarta, Indonesia. Subjects with appetite-manipulating supplements, a diet program, a history of metabolic disease, a history of eating disorders, stress, or trauma were excluded from this study. The physical activity level was evaluated using the Baecke Physical Activity Questionnaire (BPAQ), while the total food intake was evaluated using the three-day food record method. The statistical test applied in this study was the Spearman test, with a significance of p<0.05. There were 22.3% of respondents with a low physical activity level, and there were 9.7% of respondents with a total food intake higher than recommended. The statistical analysis showed a significant negative correlation between physical activity levels and total food intake (p=0.008). In conclusion, there is an association between students' physical activity levels and their total food intake.